2016
DOI: 10.1109/tnsre.2015.2493358
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vibration Exercise at Varying Frequencies by Different Fatigue Estimators

Abstract: Abstract-Vibration exercise (VE) has been suggested to improve muscle strength and power performance, due to enhanced neuromuscular demand. However, understanding of the most appropriate VE protocols is lacking, limiting the optimal use of VE in rehabilitation programs. In this study, the fatiguing effect of vibration at different frequencies was investigated by employing a force-modulation VE system. Twenty volunteers performed 12-s isometric contractions of the biceps brachii with a load consisting of a base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Only a small number of studies have investigated the fatiguing effects of vibration stimulation through the analysis of EMG frequency variables. Mischi et al and Xu et al have recently investigated the fatiguing effects of vibration through sEMG frequency analysis [15], [27]. Our study design and the vibration stimulation device differs from these earlier reported studies [15], [27].…”
Section: Overall Fatiguing Effectsmentioning
confidence: 86%
See 1 more Smart Citation
“…Only a small number of studies have investigated the fatiguing effects of vibration stimulation through the analysis of EMG frequency variables. Mischi et al and Xu et al have recently investigated the fatiguing effects of vibration through sEMG frequency analysis [15], [27]. Our study design and the vibration stimulation device differs from these earlier reported studies [15], [27].…”
Section: Overall Fatiguing Effectsmentioning
confidence: 86%
“…This might be considered a limitation. However it is important to note that a recent ULV study found no differences in the MEF, MDF and RMS values after removing the so called motion artifacts [27]. Further, another study by the same group have reported that the so called 'motion artifacts' are in fact 'stretch reflex' responses and hence filtering them might actually remove important information about stretch reflex responses and central fatigue mechanisms [25].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…To this end, the selected 12-s bipolar EMG signal (0.5-12.5 s) was first divided into a series of 1-s, overlapped epochs [33], [34]. Each epoch was moved by one sample in order to produce a continuous CV estimation, the same as the DLL system.…”
Section: ) In Vivomentioning
confidence: 99%
“…Each epoch was moved by one sample in order to produce a continuous CV estimation, the same as the DLL system. The CV in each epoch was then calculated using the ML method [34] and then compared with the CV estimated by the DLL system at the same time instant.…”
Section: ) In Vivomentioning
confidence: 99%
“…It is clear that the neuromuscular reflex response after VE remains controversial. Studies have suggested VE to produce a large degree of mechanic and myoelectric fatigue on the upper limbs while fatigue leads to decreased excitation from Ia afferents [51,42,43]. Furthermore, studies have reported increased H-reflex amplitude after non-exhausting VE possibly due to MN hyperexcitability [50].…”
Section: Introductionmentioning
confidence: 99%